Salivary Gland Ultrasonography in Sjögren's Syndrome: A European Multicenter Reliability Exercise for the HarmonicSS Project - Zabotti, Alen; Zandonella Callegher, Sara; Tullio, Annarita; Vukicevic, Arso; Hocevar, Alojzija; Milic, Vera; Cafaro, Giacomo; Carotti, Marina; Delli, Konstantina; De Lucia, Orazio; Ernst, Diana; Ferro, Francesco; et al. (Frontiers in Medicine, 2020)
Objectives Salivary gland ultrasonography (SGUS) is increasingly applied for the management of primary Sjögren's syndrome (pSS). This study aims to: i) compare the reliability between two SGUS scores; ii) test the reliability among sonographers with different levels of experience. Methods In the reliability exercise, two four-grade semi-quantitative SGUS scoring systems, namely De Vita et al. and OMERACT, were tested. The sonographers involved in work-package 7 of the HarmonicSS project from 9 countries in Europe were invited to participate. Different levels of sonographers were identified on the basis of their SGUS experience and of the knowledge of the tested scores. A dedicated atlas was used as support for SGUS scoring. Results Twenty sonographers participated in the two rounds of the reliability exercise. The intra-rater reliability for both scores was almost perfect, with a Light's kappa of 0.86 for the De Vita et al. score and 0.87 for the OMERACT score. The inter-rater reliability for the De Vita et al. and the OMERACT score was substantial with Light's Kappa of 0.75 and 0.77, respectively. Furthermore, no significant difference was noticed among sonographers with different levels of experience. Conclusion The two tested SGUS scores are reliable for the evaluation of major salivary glands in pSS, and even less-expert sonographers could be reliable if adequately instructed.